A Comparative Analysis of Clinical Outcomes between Proximal and Distal Recipient Vessel Microanastomosis for Lower Limb Reconstruction - Asirvatham, Ebenezer J. C.; Prasanth J, Bala; Philipose, Atul; Victor, Jonathan; Gupta, Ashish Kumar; Lamba, Shashank (Indian Journal of Plastic Surgery, 2025)
This study aims to compare the clinical outcomes of lower limb free-flap reconstruction with vascular anastomosis performed proximal versus distal to the zone of injury. Very few comparative studies on this topic have been published to date. These studies are discussed in this article.A retrospective analysis of microvascular free-flap reconstructions for lower extremity defects over a 5-year period, from 2018 to 2023, was conducted. Outcomes of vascular anastomosis distal to the zone of injury were compared with those proximal to the zone of injury. Clinical parameters evaluated included flap failure, arterial and venous compromise, operative takebacks, and their success rates.Of the 101 cases included in our analysis, 81 underwent vascular anastomosis proximal to the zone of injury, and 20 underwent distal anastomosis. In total, 72 (88.88%) proximal and 18 (90%) distal anastomoses were successful. Arterial thrombus occurred in 1 case (5%) among those who underwent distal anastomosis and in 4 cases (4.9%) of the proximal anastomosis cohort, whereas venous thrombus was seen in 1 case (5%) of the distal group and 12 cases (14.81%) of the proximal group. No statistically significant differences were found in clinical outcomes between the groups.Free tissue transfer using recipient vessels distal to the zone of injury is a reliable option for lower limb reconstruction. Distal anastomosis, which can be technically less challenging, demonstrates survival rates comparable to proximal anastomosis and can be considered a viable approach in selected patients.
Keywords: lower limb reconstruction; recipient vessels; distal versus proximal; anastomosis